Refund of consumption tax to low-income people: Impact assessment using difference-in-differences - Jorge Luis Tonetto; Adelar Fochezatto; Giovanni Padilha da Silva (Economies, 2023)
One way to reduce inequality and poverty is to promote tax justice. In 2021, the government of the state of Rio Grande do Sul, Brazil, implemented a program (the Devolve-ICMS Program) that refunds consumption tax to low-income citizens (cashback). This study aims to evaluate the impacts of this Program using a differences-in-differences model and having, as response variables, the monthly sum of electronic invoices issued to the Program's beneficiaries, as well as their value. The database used includes all invoices issued to the target population during the 12 months before the Program's implementation and the 14 months after its implementation, resulting in 7.7 million records. To receive the tax refund, the eligible population must pick up a Citizen Card, made available by the state government, which was done by a significant part of this population. The treatment group is composed of eligible citizens who have the Card, whereas the control group comprises eligible citizens who do not have it. The results show that the Program is effective, as it has reduced tax pressure on poor people and increased both the number of invoices issued and their value.
Keywords: 330; poverty; inequality; tax justice; difference-in-differences